O estudo das enteroparasitoses como subsídio para melhoria do ensino de Biologia e promoção da saúde - Elcy Manoel Mendes Silva (2019)
The enteroparasites represent a worldwide health problem, especially in developing countries and present a high percentage of morbidity. The occurrence of these diseases is linked to the lack or precariousness of basic sanitation, lack of personal hygiene care and lack of information on prevention, contagion and life cycle of parasites. This situation demonstrates the need to identify the occurrence of these parasitoses as well as to propose efficient strategies as a form of intervention in the transmission of these parasites. In this context, a more challenging pedagogical proposal that stimulates the protagonism of the student, becomes a tool of great importance, since it allows the acquisition of knowledge about the most diverse parasitoses, providing a change of behavior of the student in order to make him a disseminator of these ideas. The objective of this study was to use the subject of enteroparasites and its prevention to stimulate the students to carry out their learning about such content. Thirty-three students from the public school Zeca Guida enrolled in the study who attended the first and second years of high school who presented the required documentation in line with ethical aspects. The knowledge generated through the pedagogical actions developed and carried out by the students allowed the establishment of concepts related to the intestinal parasitoses making them able to transmit information about these infections to the members of the school community. The strategies of education for health promotion are efficient when guided by the stimulus to the protagonism of the students, who can identify situations in their daily life that favor the incidence of these infections and thus seek efficient measures of control and prevention.